1976
DOI: 10.1002/hlca.19760590220
|View full text |Cite
|
Sign up to set email alerts
|

Reactions with the Arylhydrazones of α‐Cyanoketones: The Structure of 2‐Arylhydrazono‐3‐ketimino‐nitriles

Abstract: Analysis of the IR., UV., and polarographic data of a variety of 2‐arylhydrazono‐3‐ketimino‐nitriles indicated that these derivatives exist mainly in the intramolecularly chelated hydrazone structure 1. Compounds 1 reacted with hydrazine hydrate to yield the corresponding 5‐amino‐4‐arylazopyrazoles (3). Compounds 3a reacted with acetylacetone, ethyl acetoacetate, and diethyl malonate to yield the pyrazolo[1, 5‐a]pyrimidine derivatives 4, 5, and 7 respectively. Compound 3a also reacted with benzoylisothiocyanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

1976
1976
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 27 publications
1
18
0
2
Order By: Relevance
“…In more recent work, Elnagdi et al (9) reported further synthetic applications of the 2-arylhydrazono-3-ketiminobutanenitrile ( l l ) , which is formally the deprotonated form of the hydrazone tautomer of the intermediate (7) The reaction of aryldiazonium salts with carbanions of Pin our proposed mechanism (Scheme 1). dicarbonyl compounds has been reported by several workers…”
Section: Resultsmentioning
confidence: 86%
“…In more recent work, Elnagdi et al (9) reported further synthetic applications of the 2-arylhydrazono-3-ketiminobutanenitrile ( l l ) , which is formally the deprotonated form of the hydrazone tautomer of the intermediate (7) The reaction of aryldiazonium salts with carbanions of Pin our proposed mechanism (Scheme 1). dicarbonyl compounds has been reported by several workers…”
Section: Resultsmentioning
confidence: 86%
“…The required 2,7-dimethyl-8-phenylazo-4(6H)-pyrazolo[1,5-a]pyrimidinone 1 was prepared by reaction of ethyl acetoacetate with 5-amino-4-arylazo-3-methyl-1H-pyrazole as previously described. 28 As no spectral data were reported for compound 1, we wish to report herein its IR, 1 H-and 13 C-NMR as well as the UV and mass spectral data (see Experimental). For example, the IR spectrum of compound 1 revealed one carbonyl band and one NH band at υ 1674 and 3228 cm -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Elemental analysis was done on a Perkin Elmer CHNS/O Analyzer 2400 Series II were recorded on Agilent 1100 MSD. 2-Arylhydrazone-3-ketiminobutyronitriles (1a-1j) and 5-amino-4-arylazo-3-methyl-1H-pyrazoles (2a-2j) were prepared according to the literature procedures [1,2]. The general route for the synthesis of 2-arylhydrazono-3-ketiminobutyronitriles and 5-amino-4-arylazo-3-methyl-1H-pyrazoles is shown in (Scheme 1).…”
Section: Synthesismentioning
confidence: 99%
“…The other λmax values of 3101-3022 cm -1 (aromatic C-H) and 2994-2963 cm -1 (aliphatic C-H) were recorded. 1 H NMR spectra of dyes 5a-5j showed four broad peaks at 12.75-10.23 ppm (NH), 11.20-9.30 ppm (NH) and two broad peaks at 7.9-8.9 ppm (OH), 10.5-11.2 ppm (OH), 0.86-0.96 ppm (CH3), 1.24-1.89 ppm (CH2), respectively. The other δ values of 2.48-2.40 ppm (CH3) and 8.35-6.98 ppm (aromatic H) were recorded.…”
Section: Spectral Characteristics and Tautomerismmentioning
confidence: 99%
See 1 more Smart Citation